Correlation between Aerial Insecticide Spraying to Interrupt West Nile Virus Transmission and Emergency Department Visits in Sacramento County, California. (May 2013) - Geraghty, Estella M.; Margolis, Helene G.; Kjemtrup, Anne; Reisen, William; Franks, Peter
Objectives: Insecticides reduce vector-borne pathogen transmission but also pose health risks. In August 2005, Sacramento County, California, underwent emergency aerial ultralow-volume (ULV) application of pyrethrin insecticide to reduce the population of West Nile virus (WNV)-infected mosquitoes and thereby interrupt enzootic and tangential transmission. We assessed the association between aerially applied pyrethrin insecticide and patterns of emergency department (ED) visit diagnoses. Methods: We used geographic information systems software to determine ZIP Code-level exposure to pyrethrin. We used logistic regression models to examine the relationship between exposure status and three-digit International Classification of Diseases, Ninth Edition, Clinical Modification (ICD-9-CM) codes (785 in total) for all ED visits ( n =253, 648) within Sacramento County in 2005 and for specific diagnostic clusters (e.g., respiratory, gastrointestinal, skin, eye, and neurologic). All models were adjusted for age, gender, race/ethnicity (individual level), median income, ozone, and temperature (ZIP Code level). Results: Exposure to aerially applied insecticide was not associated with clusters of respiratory, gastrointestinal, skin, eye, and neurologic complaints in adjusted models but was inversely associated with ICD-9-CM code 799 ("other ill-defined morbidity and mortality"), with adjusted odds ratios (AORs) ranging from 0.31 to 0.36 for 0–3 lag days (95% confidence interval 0.17, 0.68). Spraying was also directly associated with ICD-9-CM code 553 ("other abdominal hernia"), with AORs ranging from 2.34 to 2.96 for 2–3 lag days. Conclusions: The observed significant ICD-9-CM code associations likely represented chance findings. Aerial ULV pyrethrin applications were not associated with ED visits for specific diagnoses or clusters of diagnoses.